2019
DOI: 10.1039/c9ob01220f
|View full text |Cite
|
Sign up to set email alerts
|

Formation of i-motifs from acyclic (l)-threoninol nucleic acids

Abstract: Acyclic (l)-threoninol nucleic acids ((l)-aTNA) containing poly-cytosines are prepared and investigated at various pH values, revealing the formation of a highly stable structure at lower pH that have the characteristics of an i-motif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The Gothelf group found that L-aTNA forms a stable triplex when a homopyrimidine L-aTNA targets a homo-purine DNA or RNA. 57 The same group also reported that L-aTNAs of appropriate sequence can form G-quartet 58 and i-motif 59 structures. These data suggest that L-aTNA and SNA prefer to form higher-ordered structures.…”
Section: Feature Article Chemcommmentioning
confidence: 87%
“…The Gothelf group found that L-aTNA forms a stable triplex when a homopyrimidine L-aTNA targets a homo-purine DNA or RNA. 57 The same group also reported that L-aTNAs of appropriate sequence can form G-quartet 58 and i-motif 59 structures. These data suggest that L-aTNA and SNA prefer to form higher-ordered structures.…”
Section: Feature Article Chemcommmentioning
confidence: 87%
“…We also observed unusual triple base pairing, Watson‐Crick C : G and parallel Hoogsteen G*G, in solutions of L‐ a TNA/RNA and SNA/RNA confirmed by crystal structures and mass spectroscopy. Formation of higher‐ordered structures of a TNA such as conventional poly purine/pyrimidine triplex, [51] i‐motif‐like complex, [52] and G‐quadruplex‐like structure [53] were also detected by Gothelf's group. The flexible acyclic scaffold of a TNA apparently allow formation of these non‐canonical structures.…”
Section: Negatively Charged Acyclic Xna Oligomersmentioning
confidence: 92%
“…were the first to report on the synthesis of aTNA and that aTNA forms an antiparallel homo‐duplex of high stability [17, 18] . We have later shown that aTNA forms highly stable sandwich type triplex structures with DNA and RNA and that aTNA is capable of forming i‐motifs and G‐quadruplexes [19–22] . This artificial oligonucleotide furthermore forms parallel duplexes with DNA and RNA, presumably because of an optimal rigidity [17] .…”
Section: Figurementioning
confidence: 95%